Analysis of the economic impact of water management policy on residential prices: Modifying choice set formation in a discrete house choice analysis. (December 2019) - Kim, Hyun No; Boxall, Peter C.; Adamowicz, W.L.(Vic)
Abstract: This paper extends discrete residential choice models by incorporating choice set formation. Most discrete residential choice models make relatively arbitrary assumptions about the choice set – the set of houses to be considered by the purchaser. In this paper we explore several formulations of endogenous choice sets in which the decision maker's selection of a choice set is based on certain attributes and the final selection is made from this reduced choice set. The proposed approach is empirically applied to a housing transaction dataset and welfare measures are generated for non-marginal changes associated with a water management policy. A comparison of models across different temporal windows to define an individual's choice set shows that model parameters are sensitive to the assumptions used to define the choice sets. The models that approximate choice set formation improve the efficiency of estimation and influence estimated welfare measures suggesting the importance of choice set formation in the context of discrete housing choice models.